Politeness Maxims in the Motive the Forest - Pramiwidari, Ni Wayan (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p27, 2018)
The title of this undergraduate thesis is “Politeness Maxims in Different Setting of “The Forest movie“, which in this writing discussed about the use of Politeness Maxims. The aims of this thesis are to find out about the types and functions of Politeness Maxims and also to analyze the influences of the use of Politeness Maxims in different setting of The Forest movie. The theory used in this undergraduate thesis is The Theory Proposal by Geoffrey Leech. The data in this study were taken from ”The Forest movie“. The conversations that chosen in this study are implied Politeness Maxims. The data were analyzed based on six maxims stated by leech and then presented descriptively. The result of the analysis shows that there are many expressions of politeness found in “The Forest movie”. The characters in “The Forest movie” used politeness maxims more frequently. They talk more politely when they had conversation each other. It was also related to their setting which are famous to their eastern culture. The different setting in this movie also influenced the characters when they had conversations, they had to use Politeness Maxims especially when they talked to other people who were from high class or different social status.